The New Shop Class Getting Started with 3D Printing, Arduino, and Wearable Tech - Horvath, Joan; Cameron, Richard; Adrianson, Doug (Apress : Imprint: Apress, 2015)
The New Shop Class connects the worlds of the maker and hacker with that of the scientist and engineer. If you are a parent or educator or a budding maker yourself, and you feel overwhelmed with all of the possible technologies, this book will get you started with clear discussions of what open source technologies like 3D printers, Arduinos, robots and wearable tech can really do in the right hands. Written by real "rocket scientist" Joan Horvath, author of Mastering 3D Printing, and 3D printing expert Rich Cameron (AKA whosawhatsis), The New Shop Class is a friendly, down-to-earth chat about how hands-on making things can lead to a science career. Get practical suggestions about how to use technologies like 3D printing, Arduino, and simple electronics Learn how to stay a step ahead of the young makers in your life and how to encourage them in maker activities Discover how engineers and scientists got their start, and how their mindsets mirror that of the maker.